The first years of liver transplantation: experiences at a single center - Phu Hong Pham; Nghia Phuoc Phan; Viet Doan Khac Tran; Viet Quoc Dang; Dat Tien Le; Thuan Duc Nguyen; Long Cong Duy Tran; Bac Hoang Nguyen (Korean Journal of Transplantation, 2022)
Background : The aim of this study was to analyze the first stages of progress in liver transplantation (LT) at a single center in Vietnam. Methods : This study analyzed data from patients and donors who participated in the LT program between August 2018 and December 2021 at University Medical Center, Ho Chi Minh City. Study measures included any difficulties encountered, as well as the post-LT outcomes for living donor LT (LDLT) and deceased donor LT (DDLT). The chi-square test and Kaplan Meier survival analysis were used to test the factors that influenced the outcomes. Results : A total of 18 adult recipients with LT (LDLT, n=16; DDLT, n=2) were included (mean age, 55.2±2.6 years; male, 88.9%). The most common post-LT complications were middle hepatic venous stenosis (20%) and graft rejection (22.2%). These complications were observed in LDLT patients. For DDLT, graft rejection (50%) was the only complication recorded. The survival rates for recipients at 3 months, 6 months, and 1 year were 100%, 88.9%, and 88.9%, respectively. The LDs had their right livers without the middle hepatic veins harvested, and biliary leakage (6.25%) was the only complication observed. There were no deaths among recipients or LDs during the operations or hospital stays. Conclusions: This study provides key details about the process of LT, and these positive outcomes support LT as an important therapy for end-stage liver disease and early hepatocellular carcinomas.